PENGARUH EMPLOYEE ENGAGEMENT DAN KOMPETENSI TERHADAP KINERJA PEGAWAI MELALUI GOOD GOVERNANCE SEBAGAI VARIABEL INTERVENING (Studi pada Pegawai Kantor Kecamatan Prigen Kabupaten Pasuruan) - Heri Santoso,; Nasharuddin Mas,; Muchlis Mas’ud, (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
This study aims to obtain empirical evidence of the effect of employee engagement and competence on employee performance at the Prigen District Office, Pasuruan Regency through good governance as an intervening variable.The type of research used in this research is explanatory research. The population in this study were all employees of the Prigen District Office, Pasuruan Regency, totaling 33 employees. The researcher chose the sample using the saturated sampling technique because the population was relatively small. So that the sample used in this study amounted to 33 respondents. The data analysis technique used in this research is Partial Least Square-Structural Equation Modeling (PLS-SEM) using smartPLS version 3 software.The results of the study indicate that employee engagement is able to encourage an increase in employee performance. Competence is able to encourage employee performance improvement. Employee engagement is able to encourage the improvement of good governance. Competence is not able to encourage the improvement of good governance. Good governance is able to encourage the improvement of employee performance. Good governance is able to mediate the effect of employee engagement on employee performance. Good governance is not able to mediate the effect of competence on employee performance